2005
DOI: 10.1021/cm0511217
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethene Hydrodechlorination in Water by Highly Disordered Monometallic Nanoiron

Abstract: The small size and high surface-to-volume ratio makes nanoiron attractive for in situ remediation of groundwater contaminants that are susceptible to reductive transformation, e.g. trichloroethylene (TCE). Nanoiron synthesized from borohydride reduction of dissolved iron is the most widely studied. Its reactivity with chlorinated organics such as trichloroethylene (TCE) is unique compared to other nanoiron and to iron filings that are typically used for in situ groundwater remediation, e.g. (1) higher surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 37 publications
11
149
1
2
Order By: Relevance
“…It has been shown that various active metallic nanoparticles can react with chlorinated liquids and reduce them to significantly less toxic compounds. [451][452][453][454] Iron nanoparticles are very useful, but to be effective in groundwater treatment they need to be dispersable in water at a broad pH range and in the presence of various electrolytes, transportable through a watersaturated porous matrix (soil), and to have an affinity for the water-DNAPL interface. The particles should also be stable toward oxidation.…”
Section: Materials For Water Purificationmentioning
confidence: 99%
“…It has been shown that various active metallic nanoparticles can react with chlorinated liquids and reduce them to significantly less toxic compounds. [451][452][453][454] Iron nanoparticles are very useful, but to be effective in groundwater treatment they need to be dispersable in water at a broad pH range and in the presence of various electrolytes, transportable through a watersaturated porous matrix (soil), and to have an affinity for the water-DNAPL interface. The particles should also be stable toward oxidation.…”
Section: Materials For Water Purificationmentioning
confidence: 99%
“…With the development of advanced nanotechnologies since late nineties, due to their size and reactivity that allowed an easy injection,zero valent iron nanoparticles (nZVI) were considered a promising step forward in soil and groundwater clean-up, particularly targeting organochlorines [4][5][6][7][8]. The nZVI transport in porous media was studied in column tests with sand [9][10][11][12][13][14][15][16], glass beads [17][18][19] and model soils [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, better reactivity has been reported to highly disordered Fe compared with crystalline nZVI obtained by H reduction of iron oxides (Liu et al 2005a ) or by vacuum annealed Fe (Liu et al 2005b ), although in the latter case the reactivity against some pollutants seems to be unaffected by crystallization during annealing (Dickinson and Scott 2011 ). In the case of M48h-Al O (Fig.…”
Section: Tablementioning
confidence: 91%
“…The specific surface area (SSA) was analysed by BET gas adsorption drying the ethanol suspension with a maximum degassing temperature of 100 °C (ASAP 2020, Micromeritics). The Fe (0) content was determined in triplicate by the hydrogen production method (Liu et al 2005a ) where iron reacts with sulphuric acid added to the slurry and the volume of produced hydrogen was measured. The morphology of the milled particles was studied by Scanning Electron Microscopy (SEM) (Gemini, Zeiss).…”
Section: Nzvi Nanostructured Iron Milling Environmental Remediation Cmentioning
confidence: 99%
See 1 more Smart Citation